2013
DOI: 10.1016/j.jmr.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine interactions of narrow-line trityl radical with solvent molecules

Abstract: The electron nuclear dipolar interactions responsible for some dynamic nuclear polarization (DNP) mechanisms also are responsible for the presence formally in CW EPR spectra of forbidden satellite lines in which both the electron spin and a nuclear spin flip. Such lines arising from 1H nuclei are easily resolved in CW EPR measurements of trityl radicals, a popular family of DNP reagents. The satellite lines overlap some of the hyperfine features from 13C in natural abundance in the trityl radical, but their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 35 publications
(56 reference statements)
2
45
0
Order By: Relevance
“…In contrast, trityl has a maximum proton hyperfine coupling of 0.05 MHz. 33 As we will see below this is the likely source of the Overhauser effect observed in the SA-BDPA and BDPA and absent in trityl OX063. The fact that there is a large enhancement at ω 0S could possibly be explained as electron decoupling and is discussed in Ref.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, trityl has a maximum proton hyperfine coupling of 0.05 MHz. 33 As we will see below this is the likely source of the Overhauser effect observed in the SA-BDPA and BDPA and absent in trityl OX063. The fact that there is a large enhancement at ω 0S could possibly be explained as electron decoupling and is discussed in Ref.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, the lineshape is characteristic of an OE in which the sign of the DNP enhancement does not depend upon the offset of the microwave frequency. Interestingly, trityl OX063 radical, 31 which was designed to optimize Overhauser effects in solution by eliminating hyperfine couplings, 32,33 shows only SE enhancements at ω 0S ± ω 0I . Thus, the OE effect appears to require the presence of multiple hyperfine or dipolar couplings that permit zero quantum (ZQ) or double quantum (DQ) relaxation, respectively, and Overhauser enhancements.…”
Section: Introductionmentioning
confidence: 99%
“…For nitroxide radicals the unpaired spin density is localized mainly on the N-O bond [32] and in a bis-nitroxide the exchange interaction between the nitroxides is smaller than the dipolar coupling, which is about 35 MHz for AMUPol. [26] However, the unpaired spin density in a trityl radical is highly delocalized, [33] [34] which means that in a TEMTriPol biradical the exchange interaction between the two radical moieties can easily be large. Using X-band EPR spectroscopy in solution at T = 279 K, Liu et al determined the average strength of this interaction for the TEMTriPol biradicals (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, radicals with minimized intramolecular hyperfine couplings are expected to give significantly improved DNP enhancements especially at low magnetic fields/low microwave frequencies. Such a radical is the so-called Finland trityl, for which it was shown that in methanol-D 4 intramolecular hyperfine couplings have coupling constants of less than 1.4 MHz and isotropic averages of less than 0.15 MHz [33], experiments along these lines will be performed in the near future. A detailed discussion of DNP with PB and BDPA radical at 9.7 GHz will be presented in a forthcoming publication.…”
Section: Resultsmentioning
confidence: 99%